Chapter Il Musil di Claudio Magris - Di Noi, Barbara (Biblioteca di Studi di Filologia Moderna, 2021)
This paper discusses the importance and frequency of Magris' explorations of Musil and his major work as a novelist, Der Mann ohne Eigenschaften. It investigates the reasons why Musil's novel is so important, and not only so for the Germanist. Indeed, Musil's work and its interpretation can also be considered as a kind of 'model' for the writer that Magris would become later on in his career. The paper focuses on different features of Musil's masterpiece, which better meet Magris' ideal of diegesis, and somehow subvert the classic and rational paradigm of the Bildungsroman, pointing to the magic realism of a writer like Borges.